ʺThe essence of the terms “Сoncept”, “Pedagogical concept” and “Education”ʺ - Prokopenko , A. (Problems of Engineer-Pedagogical Education, 2022)
The author clarifies the essence of the terms “concept”, “pedagogical concept” and “education” on the basis of the analysis of scientific-pedagogical and specialized literature. The researcher defines “concept” as a leading idea of any theory; a system of social and value-oriented / general scientific views or as a means / form of understanding, interpreting certain phenomena / processes in the nature and society. Based on research works of domestic and foreign scientists, the author proves that “pedagogical concept” is a kind of reference point of any scientific and pedagogical research which also contributes to the effective solution of problems and helps achieve expected outcomes under the conditions of the current education reform. The article defines “pedagogical concept” as a current, priority direction of education development (it determines the purpose; problems that need to be solved; tasks, ways and means of solving them; expected outcomes); an advanced, avant-garde idea of pedagogical science; a process of determining the essence of certain pedagogical phenomena; a complex interconnected system of views on a pedagogical phenomenon, which requires improvement / modernization / introduction of significant innovations, etc. and consists, for example, of methodological, theoretical and technological concepts. “Pedagogical system” and “pedagogical concept” are claimed to be closely interrelated, but it must be noted that the term “pedagogical concept” is somewhat broader, as its content embraces all the elements and characteristics of the pedagogical system, and in some definitions of this category even includes the concept of “system”. The author defines “education” as a continuous triune educational process (training, upbringing, development), aimed at making an individual thrive. Prospects for further research are seen in the development of a pedagogical concept of education of future professionals.